Dependencies in language: On the causal ontology of linguistic systems - Enfield, N.J (Studies in Diversity Linguistics, 2017)
Dependency is a fundamental concept in the analysis of linguistic systems. The many if-then statements offered in typology and grammar-writing imply a causally real notion of dependency that is central to the claim being made-usually with reference to widely varying timescales and types of processes. But despite the importance of the concept of dependency in our work, its nature is seldom defined or made explicit. This book brings together experts on language, representing descriptive linguistics, language typology, functional/cognitive linguistics, cognitive science, research on gesture and other semiotic systems, developmental psychology, psycholinguistics, and linguistic anthropology to address the following question: What kinds of dependencies exist among language-related systems, and how do we define and explain them in natural, causal terms?